Molecular and pathological study of Providencia alcalifaciens isolated from Cyprinus carpio - Almohammadi, Ameer; Al-Taee, Shahbaa Kh; Rasheed, Balsam Y. (Iraqi journal of veterinary sciences, 2026)
A disease recorded in Cyprinus carpio during the survey period from September to December, 2024 at the commercial fish earthen pond in Khazir area in Erbil province -Iraq with high mortalities of 75 %. The goal of the study was to isolate and molecular identify the pathogen that causes fish mortality and study the histopathological alteration in the liver and kidney (naturally and experimentally infections). Gram-negative bacteria and urease-positive with Providencia bacteria colony as small, convex, pale in color, and non-fermenting lactose sugar was isolated from MacConkey agar medium. The diseased carp was lethargy with petechial hemorrhage at the basis's fins. The pathogen species was identified via biochemical responses and amplification 16S rRNA locus by PCR, a novel genome PV101576 and PV101577 were identified in (naturally and experimentally infections) respectively, and phylogenetic analysis reveal its relationship with Providencia alcalifaciens in NCBI database. Experimental infection assays with naturally infection isolate were conducted and pathogenicity by immersion 6×108 CFU/ml was demonstrated in healthy carp fish for seven day. Histopathological analysis reveals proliferative melanomacrophage, infiltration of inflammatory cell with renal and hepatopancreatic steatosis, renal cyst forming with circulatory disturbances. Conclusion of this study investigated that the Providencia-infection may be due to handling practices and ecosystem pollution, and from feces of the human and animal from adjacent fish culture. Therefore, Providencia isolate is regarded as an opportunistic bacterium for carp and lead to histological architecture alteration. This is the first investigation of Providencia that cause infections in carp farms.